Evidences, Methodologies, Analysis, and the Joy of Historical Research: An Interview with Noble David Cook - Lerner Patrón, Adrián (2020)
Noble David Cook is a leading historian of the demographic and social history of the Andes and the Atlantic World. In this interview, he discusses the origins of his interest in the histories of Peru, the Andes, and the Iberian Atlantic; the methodological approaches that influenced his work; how he sees the evolution, present and future of the fields of demographic history and Colonial Latin America; the role of the archive in his career; his vital and intellectual links with the city of Sevilla; his collaborations with his wife Alexandra Parma Cook; his long history of engagement with Peruvian scholars; and his perspectives on the current COVID-19 crisis.